Computed tomographic parameters correlate with coagulation disorders in isolated traumatic brain injury. (3rd August 2022) - Cui, Wenxing; Shi, Yingwu; Zhao, Baocheng; Luo, Jianing; Zhu, Gang; Guo, Hao; Wang, Bao; Yang, Chen; Li, Zhihong; Wang, Liang; Qu, Yan; Ge, Shunnan
Abstract: Background and Objective: The imbalanced hemostatic equilibrium caused by brain tissue or vessel damage underlies the pathophysiology of traumatic brain injury (TBI)-induced coagulopathy, and cranial computed tomography (CT) is the gold standard for evaluating brain injury. The present study aimed to explore the correlation between quantitative cranial CT parameters and coagulopathy after TBI. Methods: We retrospectively collected the medical records of TBI patients with extracranial abbreviated injury scale (AIS) scores <3 who were admitted to our institution. The quantitative cranial CT parameters of patients with and without coagulopathy were compared, and univariate correlation analysis between CT parameters and coagulation subtest values and platelet counts was performed. The predictors for each subtest of coagulation function were probed by multivariate regression. Results: TBI patients with coagulopathy had a larger intracerebral haematoma/contusion (ICH/C) volume ( p < 0.001), a higher incidence of compressed basal cisterns ( p = 0.015), a higher Graeb score ( p < 0.001) and subarachnoid haematoma (Fisher's scaling score) ( p = 0.019) than those without coagulopathy. IH/C volume was identified as an independent risk factor for predicting coagulopathy. ICH/C volume showed a significantly positive correlation with APTT (Pearson's correlation = 0.333, p < 0.001), while a significant negative correlation with PLT (Pearson's correlation = − 0.312, p < 0.001). Conclusion: ICH/C volume was a main quantitative cranial CT parameter for predicting coagulopathy, suggesting that parenchymal brain damage and vessel injury were closely associated with coagulopathy after TBI.